The change in the surface topography of magnesium under high-flux C ion irradiation - Potemkin G. V. Gely Valerjyanovich; Ligachev A. E.; Zhidkov M. V.; Kolobov Y. R.; Remnev G. E. Gennady Efimovich; Gazizova M. Y.; Bozhko S. A.; Pavlov S. K. Sergey Konstantinovich (2015, 2015)
Title screen